The effect of credit and liquidity risk on bank's financial performance: the case of Indonesian banks in buku 3 and 4 - Dayuwati, Galia Surya; Rahadi, Raden Aswin (Journal of Business and Management, 2020)
Abstract. In 2019, global growth weakened to 2.4 per cent, which affected banks in Indonesia. It is said that banks with strong liquidity must be careful, especially BUKU 3 and BUKU 4 banks since the liquidity of these banks was still relatively high; those are 103.49% and 91.81%. With the strict Liquidity risk, BUKU 3 and BUKU 4, it is necessary to see how much influence liquidity and credit risk has on the performance of BUKU 3 and 4 banks. Thus, the banks were able to do risk mapping and immediately mitigated the risk to improve bank performance and avoid default risk. In conducting this research, the data are gathered in the form of financial statements released by each bank sample found on each Bank's website and OJK website. The range of the data gathered is from 2015- 2019 in the five years of the published financial statement from 32 sample Banks categorized in BUKU 3 and BUKU 4 banks. This research uses panel regression to test each hypothesis. The result of this research shows that credit risk, which is represented by NPL Ratio, has a significant negative effect with ROA and ROE. At the same time, the liquidity ratio has a significant and positive effect on ROA and ROE. The effect of Bank Capital has a positive impact on ROA. While Bank Size does not affect all dependent variables partially but simultaneously affects ROA, ROE, and NIM. Meanwhile, the NIM variable is partially not affected by each independent variable. However, simultaneously, NIM is affected by all independent variables in this study. From the result, the author recommended each Bank needs to improve the credit monitoring process, in order to minimize credit risk and to overcome this liquidity risk, banks must seek other funding such as issuing sub-debt (debt securities), bonds, and increase capital.Keywords: Credit Risk, Liquidity Risk, Return on Asset, Return on Equity, Net Interest Margin, Bank's Performance